Bubonic panic : when plague invaded America - Jarrow, Gail (Calkins Creek, 2016)
Explores the history and causes of the bubonic plague and the 1900 scare when a man in San Francisco's Chinatown was found with it. Chronicles the successful efforts of early twentieth-century doctors who tracked and suppressed the plague from spreading in the United States.